Individual differences in the attentional modulation of the human auditory brainstem response to speech inform on speech-in-noise deficits - Saiz,Alia M; Forte,A; Reichenbach,J (Scientific Reports, 2019)
People with normal hearing thresholds can nonetheless have difficulty with understanding speech in noisy backgrounds. The origins of such supra-threshold hearing deficits remain largely unclear. Previously we showed that the auditory brainstem response to running speech is modulated by selective attention, evidencing a subcortical mechanism that contributes to speech-in-noise comprehension. We observed, however, significant variation in the magnitude of the brainstem’s attentional modulation between the different volunteers. Here we show that this variability relates to the ability of the subjects to understand speech in background noise. In particular, we assessed 43 young human volunteers with normal hearing thresholds for their speech-in-noise comprehension. We also recorded their auditory 30brainstem responses to running speech when selectively attending to one of two competing voices. To control for potential peripheral hearing deficits, and in particular for cochlear synaptopathy, we further assessed noise exposure, the temporal sensitivity threshold, the middle-ear muscle reflex, and the auditory-brainstem response to clicks in various levels of background noise. These tests did not show evidence for cochlear synaptopathy amongst the volunteers. Furthermore, we found that only the attentional modulation of the brainstem response to speech was significantly related to speech-in-noise comprehension. Our results therefore evidence an impact of top-down modulation of brainstem activity on the variability in speech-in-noise comprehension amongst the subjects.